Pengaruh Tingkat Pendidikan Ibu Terhadap Kejadian Stunting di Kabupaten Lombok Barat Menggunakan Metode Regresi Logistik - Ade Irawan; Miftha Sukma Adi Prajanati; Badrun Islami; Musparlin Halid (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Stunting is a chronic nutritional problem that has an impact on the impaired physical and cognitive growth of children. West Nusa Tenggara (NTB) is one of the provinces that makes stunting a major health problem. Based on the 2022 SSGI report, the prevalence of stunting in NTB is very high because it exceeds the national target figure, despite a downward trend in recent years. Factors such as lack of nutritional knowledge, basic sanitation, improper parenting habits, and low maternal education are also the main causes. One of the factors that is often associated is the low level of education of mothers. Low maternal education has an impact on the quality of parenting and the fulfillment of children's nutritional needs. This emphasized the urgency of analyzing the influence of maternal education level on stunting incidence in West Lombok Regency. The method used to determine the influence of maternal education level on stunting incidence uses the logistic regression analysis method. Logistic regression analysis is a data analysis method that is able to determine the influence of independent variables (maternal education) on dependent variables (stunting events) that are categorical. The results of the study show that there is an influence on the level of education of mothers on the incidence of stunting. This is based on a p-value of 0.001 and an OR of 0.214.